The Bioferias and its potential to promote the consumption of agroecological produce in Quito - Vasco, Cristian (2019)
With data from a survey conducted in April-May 2017 among the costumers of farmers’ markets, we analyzed the motivations for the consumption of agroecological foodstuffs in Quito, Ecuador. The results reveal that agroecological consumers substantially differ from the rest of the population in terms of education and income. The principal motivations to buy in agroecological farmers’ markets is that agroecological produce is perceived as healthier than conventionally produced food. On the other hand, environmental concern is the least important motivation to consume agroecological food. Additionally, the results of a linear regression model show that educated individuals with higher incomes that belong to a social/environmental are those who spend the most on agroecological products.